Hardness, Density and Water Absorption Properties of Doum Palm Shell Particles and Sugarcane Bagasse Reinforced Polypropylene Hybrid Composite - Kyari, K. R.; Aji, I. S.; Daura, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT)
Agricultural waste issues have been a subject of discussion mainly on its conversion to wealth because of some environmental problems associated with it. The use of natural fibers and agricultural wastes for the formulation of composites materials has therefore continue to receive great attention. This work is focused on the utilization of Doum Palm shell particles and Sugarcane Bagasse to reinforce polypropylene (PP) in the production of a hybrid composite. The influence of material loading on the hardness, density and water absorption properties of the composite was studied. The composites were set by compounding PP and Doum Palm shell particles using compression moulding technique. The particulate size of the filler materials considered was 150 μm. The different material loading to matrix mixture were 10:90,20:80, 30:70, 40:60 and 50:50 respectively, after which the composites were characterized. SEM analysis was also carried out in order to know the level of interaction between the matrix and materials loaded. Analyses of variance (ANOVA) were employed for optimization of the results. Hardness of neat PP was 65Hv but gradually decreased with material loading to a value of 42.3Hv at 50wt% loading of the PP. Water absorption showed a direct proportionality with exposure time and fiber loading up to 8.49% after 14days of soaking. Material loading ensured increased density proportionally to 0.468g/cm3 at 50 wt%. The optimization result showed significant difference in most of the results obtained. It is concluded that Doum Palm shell and Sugarcane Bagasse hybrid composites have potential for industrial application.